Development of a robust chromatographic method for the detection of chlorophenols in cork oak forest soils. - McLellan, Iain; Hursthouse, Andrew; Morrison, Calum; Varela, Adélia; Pereira, Cristina Silva (Environmental monitoring and assessment, 2014)
A major concern for the cork and wine industry is 'cork taint' which is associated with chloroanisoles, the microbial degradation metabolites of chlorophenols. The use of chlorophenolic compounds as pesticides within cork forests was prohibited in 1993 in the European Union (EU) following the introduction of industry guidance. However, cork produced outside the EU is still thought to be affected and simple, robust methods for chlorophenol analysis are required for wider environmental assessment by industry and local environmental regulators. Soil samples were collected from three common-use forests in Tunisia and from one privately owned forest in Sardinia, providing examples of varied management practice and degree of human intervention. These provided challenge samples for the optimisation of a HPLC-UV detection method. It produced recoveries consistently >75 % against a soil CRM (ERM-CC008) for pentachlorophenol. The optimised method, with ultraviolet (diode array) detection is able to separate and quantify 16 different chlorophenols at field concentrations greater than the limits of detection ranging from 6.5 to 191.3 μg/kg (dry weight). Application to a range of field samples demonstrated the absence of widespread contamination in forest soils at sites sampled in Sardinia and Tunisia.
Keywords: chlorophenols; Cork oak; hplc; method development; NATO Science for peace; Quercus Suber L; soils

Avaliação do Potencial de Actividades em Sistemas de Uso Múltiplo: Aptidão Forrageira - Alpendre, Pedro; Gonçalves, Ana Cristina; Ferreira, Alfredo Gonçalves; Dias, Susana Saraiva (Silva Lusitana, 2008)
Multiple use systems are characterised by the presence of several cultures in a management unit. These cultures present their own characteristics and several productions, with different spatial and temporal arrangements. In Alentejo the most representative systems, in terms of area, are the "montados", agro-silvo-pastoral systems, characterised by three main components, forest, agriculture and grazing, and the interrelations among them. In these systems the grazing component and, consequently, the pasture is a fundamental activity for the system maintenance/perpetuity. The goal of this study is to create a methodology that defines the forage aptitude of the "montado", as function of the soil and forest cover. The utilisation of spatial analysis processes, in geographical information systems, allowed the development of an innovative methodology, constituting an evaluation and implementation information tool.
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: activités en systèmes d; aptitude de; evaluation du potentiel des; evaluation tool; forage aptitude; forest cover; GIS; les systèmes d; par la présence de; plusieurs cultures; production fourragère; résumé; soils; usage multiple; usage multiple sont caractérisés

Avaliação do Potencial de Actividades em Sistemas de Uso Múltiplo: Aptidão Forrageira - Alpendre, Pedro; Gonçalves, Ana Cristina; Ferreira, Alfredo Gonçalves; Dias, Susana Saraiva (Silva Lusitana, 2008)
Multiple use systems are characterised by the presence of several cultures in a management unit. These cultures present their own characteristics and several productions, with different spatial and temporal arrangements. In Alentejo the most representative systems, in terms of area, are the "montados", agro-silvo-pastoral systems, characterised by three main components, forest, agriculture and grazing, and the interrelations among them. In these systems the grazing component and, consequently, the pasture is a fundamental activity for the system maintenance/perpetuity. The goal of this study is to create a methodology that defines the forage aptitude of the "montado", as function of the soil and forest cover. The utilisation of spatial analysis processes, in geographical information systems, allowed the development of an innovative methodology, constituting an evaluation and implementation information tool.
Keywords: activités en systèmes d; aptitude de; evaluation du potentiel des; evaluation tool; forage aptitude; forest cover; GIS; les systèmes d; par la présence de; plusieurs cultures; production fourragère; résumé; soils; usage multiple; usage multiple sont caractérisés

Materia orgánica de suelos bajo encinas. Mineralización de carbono y nitrógeno - Gonzalez Parra, J; Candás Villar, M A (Forest Systems, 2008)
Soil characteristics under evergreen oaks forest (Quercus rotundifolia Lam.) located at the East of Segovia were studied. The soils were formed from gneis and limestone. The whole soil was 0-20 cm depth. The soils were classified as mollic Leptosols, eutric Cambisols and calcaric Cambisols. Horizons sequences were the following: O, Ah1, Ah2, C and O, Ah1, Ah2, BC. Organic horizons (3-0 cm depth) were formed by the not-yet decomposed organic remains from evergreen oaks. Mean organic matter content was 25%. The C:N ratio was high and free organic carbon was near 90% of the total carbon, which correspond with a low degree of humification. Soil texture was loamy sand and sandy loam. Soils on limestone present the highest clay fraction contents. The bases saturation degree was high, being Ca 2+ the fundamental cation of exchange complex. Organic matter content and C:N ratio were lower in organic minerals horizons than in organic horizons. Humification degree was 60% with a predominance of HAs over FAs. The polimerization of humic substances makes possible the formation of humus «moder». Carbon mineralization to the total C was ten times higher than nitrogen mineralization in upper horizons. In all horizons the nitrification was higher than N mineralization. Carbon mineralization was lower and N mineralization was higher in deeper horizons compearing with upper horizons.
Keywords: mineralization; nitrogen; organic matter; Quercus rotundifolia; soils

Edaphic characteristics of Quercus suber woods in Latium - Dowgiallo, G.; Testi, A.; Pesoli, P.; Pignatti, S. (Rendiconti Lincei, 1997)
{In this paper the results are reported of a soil survey done in selected sites of Latium un- der the most significant Quercus suber woods (Cytiso-Quercetum suberis Testi, Pignatti and Lucattini 1994) previously studied from a phytosociologicat point of view. After describing the dominant soil type of each area, physical-chemical characteristics have been analysed in order to point out the significance of edaphic factors in the distribution and floristic composition, of the Quereus suber co,noses. Bioclimatic, structural and edaphic features of this vegetation showed a great convergence; among all the parameters examined, AWC resulted to be the most effective one in conditioning the mesophilous character of Quercus suber coenoses growing in Latium. In this respect this type of vegetation shows rather strong affinities with mixed Quercztr cerrz} woods, both in the floristic composition and in the edaphic requirements, as already suggest- ed in the most recent phytosociological studies.
Keywords: Correlation soil-vegetation; Latium; Quercus suber oakwoods; soils

Edaphic characteristics of Quercus suber woods in Latium - Dowgiallo, G; Testi, a; Pesoli, P; Pignatti, S (Rendiconti Lincei, 1997)
{In this paper the results are reported of a soil survey done in selected sites of Latium un- der the most significant Quercus suber woods (Cytiso-Quercetum suberis Testi, Pignatti and Lucattini 1994) previously studied from a phytosociologicat point of view. After describing the dominant soil type of each area, physical-chemical characteristics have been analysed in order to point out the significance of edaphic factors in the distribution and floristic composition, of the Quereus suber co,noses. Bioclimatic, structural and edaphic features of this vegetation showed a great convergence; among all the parameters examined, AWC resulted to be the most effective one in conditioning the mesophilous character of Quercus suber coenoses growing in Latium. In this respect this type of vegetation shows rather strong affinities with mixed Quercztr cerrz} woods, both in the floristic composition and in the edaphic requirements, as already suggest- ed in the most recent phytosociological studies.
Keywords: Correlation soil-vegetation; Latium; Quercus suber oakwoods; soils